2017
DOI: 10.1016/j.jpain.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Change in “Self-as-Context” (“Perspective-Taking”) Occurs in Acceptance and Commitment Therapy for People With Chronic Pain and Is Associated With Improved Functioning

Abstract: Acceptance and Commitment Therapy (ACT) is based on the Psychological Flexibility (PF) model, which includes a therapeutic process, referred to as "self-as-context" (SAC). This study investigates whether ACT is associated with an effect on SAC and whether this effect is linked to treatment outcomes in people with chronic pain. 412 adults referred to a pain management center participated in the study. Participants completed measures of treatment processes (SAC, pain acceptance) and outcomes (pain-related interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 30 publications
6
49
0
1
Order By: Relevance
“…Higher scores reflect a greater sense of self‐as‐context. The SEQ has good internal consistency, it correlates as one would expect with other components of PF and with measures of functioning in people with chronic pain (Yu et al., ), and is sensitive to treatment effects from ACT (Yu et al., ).…”
Section: Methodsmentioning
confidence: 98%
“…Higher scores reflect a greater sense of self‐as‐context. The SEQ has good internal consistency, it correlates as one would expect with other components of PF and with measures of functioning in people with chronic pain (Yu et al., ), and is sensitive to treatment effects from ACT (Yu et al., ).…”
Section: Methodsmentioning
confidence: 98%
“…The psychological flexibility represents the ability to consciously stay in touch with the present moment, without setting up unnecessary defences, and to put in place a behavior adapted to the service of a set personal goal[18]. One of the components of the model is the committed action which is defined as a value-oriented behavior pattern, persistent in that it incorporates setbacks or discomfort[19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Another component is the contextual Self. This conceptualization of the Self is centered on the capacity of perspective-taking which entails distancing oneself from one’s thoughts[18]. Recent studies have shown favorable associations between these components, social, and physical functioning[21].…”
Section: Introductionmentioning
confidence: 99%
“…It is customarily regarded as having six facets: acceptance, cognitive defusion, present-focused awareness, a sense of self as perspective, and action qualities that are committed and values-directed (20,30). Accumulating evidence for the PF model is now quite considerable, including evidence for each of the facets listed here in their significant role in relation to the emotional, physical, and social functioning of people with chronic pain (31-33; see [34] for a recent short review).…”
Section: An Integrative Philosophy and Modelmentioning
confidence: 99%
“…More recently we have shown for the first time that change in what is called in ACT "self-ascontext," or perspective taking, combined with acceptance also correlates with improved functioning in ACT for chronic pain (34,46). Self-as-context is a process of experiencing a distinction (you are separate from) or a hierarchical arrangement (you are larger or greater than) between thoughts and feelings and the person who sees and acts on these experiences.…”
Section: Process and Mechanism In Actmentioning
confidence: 99%